2008
DOI: 10.1111/j.1551-2916.2008.02273.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Influence of Grain Boundary Geometry on the Electromagnetic Properties of Polycrystalline YBa2Cu3O7−x Films

Abstract: Shortly after the discovery of high‐temperature superconducting (HTS) materials in the late 1980s, it was revealed that grain boundaries in these complex oxides are strong barriers to current flow. This fact has remained one of the most significant challenges to a viable HTS conductor, and necessitated the development of technologies capable of producing biaxially textured substrates in long lengths. Multiple studies have reported that the critical current density (Jc) across grain boundaries in the perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Numerous experiments on bicrystals 18 showed that, depending on the grain boundary misorientation angle, the current transport is controlled by J c,GB at low fields, whereas at fields in the Tesla range J c,G limits the current transport. Although it is not fully established that the behaviour of a single well-defined grain boundary is representative for the complex grain boundary network of a coated conductor 19,20 , the current limitation by the grains and an increase of J c,G after irradiation are straightforward explanations for the observed J c improvement in high fields. Further evidence for this scenario is provided by neutron irradiation of YBCO thin films grown on single-crystalline substrates, which can be regarded as single macroscopic grains and thus serve as a model system for the individual microscopic grains in a coated conductor.…”
Section: Granularity Effectsmentioning
confidence: 99%
“…Numerous experiments on bicrystals 18 showed that, depending on the grain boundary misorientation angle, the current transport is controlled by J c,GB at low fields, whereas at fields in the Tesla range J c,G limits the current transport. Although it is not fully established that the behaviour of a single well-defined grain boundary is representative for the complex grain boundary network of a coated conductor 19,20 , the current limitation by the grains and an increase of J c,G after irradiation are straightforward explanations for the observed J c improvement in high fields. Further evidence for this scenario is provided by neutron irradiation of YBCO thin films grown on single-crystalline substrates, which can be regarded as single macroscopic grains and thus serve as a model system for the individual microscopic grains in a coated conductor.…”
Section: Granularity Effectsmentioning
confidence: 99%
“…Since w is a few microns in Nb 3 Sn, about a factor of 5 -10 larger than the grain size 54 , it suggests that several grains act together as a single channel or equivalently not all triple points separate the channels (probably because they are not aligned sufficiently with the field direction). The HTS YBCO and BiSCCO have much smaller values of w than the grain sizes in these materials [55][56][57] which implies that faceting or grain boundary dislocations divide a grain boundary into many SNS junctions, or to use the language of flux pinning, there are strong pinning sites along the grain boundaries 41,58,59 . In parameterising the free-parameter d, This paper uses a single functional form that naturally leads to power law behaviour at low field and exponential behaviour in high fields without introducing two mechanisms.…”
mentioning
confidence: 99%
“…14 However, this is a minor disadvantage considering that the transport superconducting properties are only weakly sensitive to the grain mis-orientations up to 4°. 16,17 The fluorinated metal-organic deposition ͑MOD͒ precursor layers were deposited by American Superconductor Corporation by spin-coating precursors identical to those used in the production of the second-generation superconducting wire. 18 The precursor film had the cation composition of Y:Dy:Ba:Cu=1:0.5:2:3; Dysprosium metal was added to enhance pinning at high fields, at the same time Dy addition suppressed formation of Y248-type stacking faults ͑SFs͒.…”
Section: Methodsmentioning
confidence: 99%